IDENTIFIKASI FAKTOR PENENTU KEPUTUSAN KONSUMEN DALAM MEMILIH PRODUK PERBANKAN (STUDI KASUS : MAHASISWA UIN SYARIF HIDAYATULLAH JAKARTA) - Alvin Handrianto Saputra; Rinda Hesti Kusumaningtyas; Nita Alfiani (STUDIA INFORMATIKA: JURNAL SISTEM INFORMASI, 2017)
The behavior of a bank customer to determine your decision in choosing a bank products such as funding, lending, and of this service can be affected by several factors such as consumer confidence in the banks concerned, customer satisfaction with banking services, and confidence in the experience of the previous experience of bank customers. This research aims to analyze and find out how big the influence of factors that are tested to students of UIN Syarif Hidayatullah Jakarta. This research method used is descriptive analytic method with cross sectional study design and for sampling by purposive and snowball sampling method. The results of this study can be concluded that the factor of consumer knowledge about banking products, service factor, and the location factor is affecting decision makers students of UIN Syarif Hidayatullah Jakarta in selecting a banking product with the percentage of >75%. Psychological factors only slightly influence the decision makers students of UIN Syarif Hidayatullah Jakarta in select banking products because it has a percentage of <75%. While the service factors are actors that most influence the decision makers students of UIN Syarif Hidayatullah Jakarta in selecting banking products. It can be seen from the resulting percentage value of 81.7%.